Single-layer seromuscular Continuous Versus Two-Layers Intestinal Anastomosis Of Small bowel in Baghdad Teaching Hospital (A prospective Study) - Mohammed M. Habash; Yahya K. Hammoudi; Tharwat I. Sulaiman (مجلة كلية الطب, 2014)
Background: Anastomosis may be done with the help of stapling devices, by using double layered suturing technique or by a single layer technique. Patients and methods: A prospective study conducted in Baghdad Teaching Hospital, Iraq.  A total of sixty- four patients were included in this study. They were divided into two groups; group A, 28 patients, single layer seromuscular continuous anastomosis was done and group B, 36 patients underwent conventional double layered anastomosis.Objective: The aim of the study is to prove that a single layer continuous technique can be constructed in a significantly less time with similar rate of complications compared with two layers technique.